2016
DOI: 10.5194/esurf-4-125-2016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bedrock erosion by subglacial water flow

Abstract: Abstract. Bedrock erosion by sediment-bearing subglacial water remains little-studied; however, the process is thought to contribute to bedrock erosion rates in glaciated landscapes and is implicated in the excavation of tunnel valleys and the incision of inner gorges. We adapt physics-based models of fluvial abrasion to the subglacial environment, assembling the first model designed to quantify bedrock erosion caused by transient subglacial water flow. The subglacial drainage model consists of a one-dimension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 103 publications
(230 reference statements)
1
53
0
Order By: Relevance
“…Beaud et al () developed a model of bedrock erosion by subglacial water flow using a fluvial abrasion law (Lamb, Dietrich, & Sklar, ) in a supply‐limited system. They showed that water flow‐induced abrasion rates are negligibly small at the glacier scale, compared to expected ice flow‐induced erosion rates.…”
Section: Introductionmentioning
confidence: 99%
“…Beaud et al () developed a model of bedrock erosion by subglacial water flow using a fluvial abrasion law (Lamb, Dietrich, & Sklar, ) in a supply‐limited system. They showed that water flow‐induced abrasion rates are negligibly small at the glacier scale, compared to expected ice flow‐induced erosion rates.…”
Section: Introductionmentioning
confidence: 99%
“…Subglacial drainage systems modulate ice flow (Iken and Bindschadler, 1986) and the pattern of glacial erosion (Beaud et al, 2016). The seasonal evolution and distribution of channels cut into ice (Röthlisberger channels) and their influence on ice flow (e.g., Cowton et al, 2013) is well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Predicted values of the aspect ratio decrease with increasing θ t . However, typical values of the Shields parameter in the subglacial channel environment are as yet unknown [ Beaud et al , ], although the high hydraulic pressures [>5 MPa, Walder and Fowler , ] suggest larger values than is typical for overland flows, leading to a decrease of R in comparison with fluvial systems. There is a good agreement of the model with the data, for all values of f m , at higher θ t values than those found typically in fluvial systems.…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining predictions for the minimum channel width and tributary junction angle is also challenging. In particular, deriving a successful model for the minimum channel width can prove problematic, given that the models of subglacial erosion and landscape evolution are mostly underdeveloped [ Beaud et al , ] and require a constraint on the overlying ice thickness. Although the model for the aspect ratio in equation is consistent with the data, the proportionality between R and Δ h t highlights the sensitive dependence on the lateral variations of ice thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation